OPTIMALISASI PERAN JAKSA MASUK PESANTREN DALAM PENCEGAHAN TINDAK PIDANA DI LINGKUP PESANTREN - Putri Wijaya, Dea; Lamadiri, Alanda Aldora; Febriansah, Roland; Annashrul, Fajar Luthfi; Indawati, Yana (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2024)
The prosecutor is a government agency that operates in the field of scanners. In carrying out its expertise in the intelligence sector, there is a program related to prosecutors entering Islamic boarding schools. This program is carried out so that prosecutors interact directly with the community. This program focuses on students who are in Islamic boarding school dormitories, the material provided is related to national insight and crimes such as bullying. This aims to make the students understand that in group life there are things that can happen due to intense activities. This simple impact influenced by limited circumstances and environment can lead to a tendency to commit violations of Islamic boarding school discipline, especially since the enforcement of discipline towards Islamic boarding school administrators is lower than the enforcement of discipline towards junior students. Therefore, the prosecutor’s office is carrying out this program so that there is prevention and understanding regarding this matter.